Exploring supervisory support as a moderator in the link between emotional intelligence and learning motivation - Husain, Farahiah Huda; Mokhtar, Abdul Basit; Sharif, Sabariah; Madjapuni, Mad Noor (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This study explores the moderating effect of supervisory support in the relationship between emotional intelligence (EI) and learning motivation (LM) among doctoral students in Malaysian public universities. Addressing the critical gap of low supervisory support, the framework integrates EI strategies with structured guidance to enhance academic motivation and resilience. The findings reveal that supervisory support acts as a partial moderator, with a stronger EI impact under low support conditions (β=1.040) and a reduced effect under high support (β=0.607). This innovation emphasizes the dual role of leveraging EI for emotional self-regulation and fostering effective supervisor-student relationships. Programs like those offered by 2MW Sdn. Bhd., including mentoring systems and supervisory training, showcase real-world solutions to improve supervisory practices, bridging the identified gap. Unlike traditional approaches, the framework combines emotional and academic dimensions through interactive EI training modules, supervisory support portals, and performance monitoring dashboards. These tools address the global challenge of doctoral attrition by fostering emotional well-being and creating a supportive academic ecosystem. With significant commercialization potential, this model offers scalable applications for universities worldwide, targeting reduced dropout rates and improved educational experiences. Aligning with global goals for quality education and mental health, this framework paves the way for sustainable and inclusive academic advancements.